Portfólios ponderados pelo risco: uma abordagem para a alocação de carteiras - Ariki, Rodrigo Yukio (2016)
This study investigates the performance of an investment portfolio constructed with equal contributions of risky assets to total portfolio risk (risk parity), using a sample of daily closing prices of 27 shares traded in the Brazilian stock market from January 2004 to December 2014. The study compares such a portfolio with three other portfolios constructed with more traditional approaches: the mean-variance portfolio, the minimum-variance portfolio and the equally-weighted portfolio, also known as naive portfolio. This study also examines the risk-parity portfolio’s performance in comparison with two important indicators of the Brazilian capital market: the IBOVESPA and the CDI rate. The required time series were constructed with quarterly portfolio rebalancing in order to replicate Maillard et al. (2010). The results indicate that the risk-parity portfolio did not outperform the mean- variance and minimum-variance portfolio, in terms of return and risk. On the other hand, the results indicate that the risk-parity portfolio outperformed the naïve portfolio, IBOVESPA and CDI rate and also produced similar results to those in Maillard et al. (2010). The study concludes that the risk-parity portfolio is a feasible alternative for portfolios that seek, in the long run, stability in terms of risk allocation and asset weights in various macroeconomic scenarios.